2019
DOI: 10.1093/icvts/ivz211
|View full text |Cite
|
Sign up to set email alerts
|

Comparing outcomes between valve-sparing root replacement and the Bentall procedure in proximal aortic aneurysms: systematic review and meta-analysis

Abstract: In aortic root aneurysms, the challenge of a valve-sparing aortic root replacement (VSRR) procedure is to ensure durable aortic valve function without reintervention. Although the Bentall procedure defers the durability of valve function to the prosthesis, short- and long-term complications tend to be higher. The aim of this study was to compare the outcomes of VSRR and Bentall procedures in patients with aortic root aneurysms. A systematic literature review was conducted using PubMed regarding the outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
1
19
0
3
Order By: Relevance
“…Compared with either mechanical or biological valve replacements, valve-sparing aortic root replacement has proved to be advantageous owing to its noninferior, even superior, perioperative mortality and follow-up reoperation rates, as well as lower rates of bleeding, and prosthesis-related complications, and improved quality of life. [22,23] The aortic root is a complex anatomic structure with its components: the aortoventricular junction or aortic annulus, aortic cusps, aortic commissures, aortic sinuses, and the sinotubular junction, each of which having crucial roles for competent aortic valve function, particularly coaptation. [5] All aortic root dimensions, including the effective height, have been shown to be highly patient-specific and correlated with the body weight and size, and body surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with either mechanical or biological valve replacements, valve-sparing aortic root replacement has proved to be advantageous owing to its noninferior, even superior, perioperative mortality and follow-up reoperation rates, as well as lower rates of bleeding, and prosthesis-related complications, and improved quality of life. [22,23] The aortic root is a complex anatomic structure with its components: the aortoventricular junction or aortic annulus, aortic cusps, aortic commissures, aortic sinuses, and the sinotubular junction, each of which having crucial roles for competent aortic valve function, particularly coaptation. [5] All aortic root dimensions, including the effective height, have been shown to be highly patient-specific and correlated with the body weight and size, and body surface area.…”
Section: Discussionmentioning
confidence: 99%
“…In aortic root disease, the prosthetic valve component is a major drawback and should be avoided if possible, particularly in the young. In aortic root replacement, Salsami et al 21 meta‐analysis reported a lower operative mortality, better 5‐year survival, lower thromboembolic events in favor for VSRR in comparison with Bentall; however and increase in reoperation rate was noted (odds ratio: 1.3; 95% confidence interval: 0.72–2.33).…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite the surgical advances over the years, there remains a never-ending debate about the fate of the aortic root; whether it should be repaired using a conservative root-sparing approach such as supra-commissural repair or replaced with an aggressive approach using the Bentall method or with a valve-sparing root replacement (VSRR). [2][3][4] The VSRR approach is performed using the Yacoub or David procedures, whilst the Bentall procedure includes the replacement of the aortic valve and aortic root. The conservative approach which can be termed "root-sparing repair" describes the procedure of undertaking aortic valve resuspension as part of supra-coronary repair; hence, the native root is not replaced and being left untouched.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, pursuing the extensive approach encompasses longer operating times but potentially allows reduced rates of re-operation. 2 However, there remains the controversy whether this approach can be pursued without further risk on mortality in comparison to conservative methods, with desirable outcomes, however, with possible risks of re-intervention in future.…”
Section: Introductionmentioning
confidence: 99%